Dynamic model of the commodity prices with variable delay - Barzdžiukas, Raimondas; Švitra, Osvaldas; Vilkytė, Ramunė (Lietuvos matematikos rinkinys, 2013)
In this article the authors analyses of the commodity prices growth model with delay depends on the search solution, i.e. the commodity prices. The stable periodic solution of the model is constructed with the help of the Bifurcation theory.